1991
DOI: 10.1099/00221287-137-12-2733
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a putative porcine transferrin receptor from Actinobacillus pleuropneumoniae biotype 1

Abstract: ~ ~ ~~~Each of two affinity isolation methods, the first based on biotinylated porcine transferrin plus streptavidinagarose, and the second on Sepharose-coupled porcine transferrin, followed by SDS-PAGE, allowed the isolation and identification of two potential porcine-transferrin-binding polypeptides ( -64 kDa and 99 kDa) from total membranes of Actinobaciflus pfeuropneumoniae grown under iron-restricted conditions. Both polypeptides were iron-repressible and were identified as potential receptor candidates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…Two iron-repressible porcine transferrin-binding proteins of 56 and 105 kDa, respectively, have been isolated from A. pleuropneumoniae serotypes l, 2, and 7, of which only the 56-kDa protein could be renatured to bind porcine transferrin after SDS-PAGE and Western blotting [32]. Similar results were obtained by Ricard et al [78], who reported the purification oftransferrin binding proteins of 64 and 99 kDa from A. pleuropneumoniae.…”
Section: Haemophilus and Actinobacillussupporting
confidence: 72%
See 1 more Smart Citation
“…Two iron-repressible porcine transferrin-binding proteins of 56 and 105 kDa, respectively, have been isolated from A. pleuropneumoniae serotypes l, 2, and 7, of which only the 56-kDa protein could be renatured to bind porcine transferrin after SDS-PAGE and Western blotting [32]. Similar results were obtained by Ricard et al [78], who reported the purification oftransferrin binding proteins of 64 and 99 kDa from A. pleuropneumoniae.…”
Section: Haemophilus and Actinobacillussupporting
confidence: 72%
“…Interestingly, however, strain Eagan appears to be an exception possessing TBPs of 107 kDa and 76 kDa, respectively, although the latter may represent a partially unfolded 90-kDa TBP2 [46]. The transferrin binding proteins of A.pleuropneumoniae [32,78] and 1t. somnus [70] have also been isolated using similar affinity-isolation methods but employing porcine and bovine transferrins respectively.…”
Section: Haemophilus and Actinobacillusmentioning
confidence: 99%
“…A polypeptide with an estimated molecular mass of -120 kDa was detected in total and outer membranes from all three strains but only if the membranes were from organisms grown under the conditions that promoted the expression ofHb binding activity. Unfortunately, the -120-kDa polypeptides could not be affmity-iso1ated using any of the methods described by Ricard et al (1991), Elkins (1995) or Jin et al (1996), with or without modifications.…”
Section: H Somni Can Produce An Iron-repressible -120-kda Outer-memmentioning
confidence: 99%
“…The methods of Ricard et al (1991) and Jin et al (1996), using biotinylated bovine Hb as the binding ligand, were also tried but without success. The effectiveness of the solubilizing solutions was also questioned.…”
Section: H Somni Can Produce An Iron-repressible -120-kda Outer-memmentioning
confidence: 99%
“…Tf-binding polypeptides were isolated from total membranes of H. somnus strain 649 by using the affinity procedure developed by Schryvers and Morris (22), as modified by Ricard et al (20). The membranes used in these experiments were from organisms grown under iron-restricted conditions in the presence of Tf, since such growth conditions were the only ones that yielded organisms exhibiting significant Tf-binding activity.…”
Section: Isolation and Identification Of Transferrin-binding Polypeptmentioning
confidence: 99%